Two-dimensional Materials for Photodetector - Kumar Nayak, Pramoda (IntechOpen, 2018)
Atomic thin two-dimensional (2D) materials are the thinnest forms of materials to ever occur in nature and have the potential to dramatically alter and revolutionize our material world. Some of the unique properties of these materials including wide photoresponse wavelength, passivated surfaces, strong interaction with incident light, and high mobility have created tremendous interest in photodetector application. This book provides a comprehensive state-of-the-art knowledge about photodetector technology in the range visible to infrared region using various 2D materials including graphene, transition metal dichalcogenides, III-V semiconductor, and so on. It consists of 10 chapters contributed by a team of experts in this exciting field. We believe that this book will provide new opportunities and guidance for the development of next-generation 2D photodetector.